Pemanfaatan Marketplace Shopee untuk UMKM di Kelurahan Kebonsari, Jambangan, Kota Surabaya Melalui Pendampingan dan Pelatihan Pemasaran Online - Nugroho, Novianto Eko; Cahyono, Krido Eko; Mahargiono, Pontjo Bambang; Suryawirawan, Okto Aditya (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This community service activity aims to improve the knowledge and skills of MSME actors in RT. 07 RW. 01, Kebonsari Jambangan Village, Surabaya City, in utilizing the Shopee e-commerce platform to increase sales and competitiveness of their products. The training and mentoring methods are structured through lectures, demonstrations, and practice. The results of the community service activity are an increase in participants' understanding and skills in using the Shopee application. Participants are able to create and manage online stores, implement effective marketing strategies, and increase product sales and market reach. These findings indicate that structured training and mentoring in using e-commerce platforms such as Shopee can provide significant benefits for MSMEs by increasing their sales and market reach.